Culturable root endophyte communities are shaped by both warming and plant host identity in the Rocky Mountains, USA. (February 2021) - Lyons, Kelly G.; Mann, Michael; Lenihan, Molly; Roybal, Olivia; Carroll, Kelly; Reynoso, Kyle; Kivlin, Stephanie N.; Taylor, D. Lee; Rudgers, Jennifer A.
Abstract: Understanding the biogeographic patterns of root-associated fungi and their sensitivity to temperature may improve predictions of future changes in terrestrial biodiversity and associated ecosystem processes, but data are currently limited. Anticipating change will require combining observational data, which predict how climatic factors limit current species distributions, with direct manipulations of climate, which can isolate responses to specific climate variables. Root endophytes are common symbionts of plants, particularly in arctic and alpine environments, yet their responses to climate warming are not resolved. Here, we directly cultured endophytic fungi from roots collected along altitudinal gradients in replicated mountain watersheds and from a 27 y field warming experiment in the Rocky Mountains, USA, to improve understanding of climate impacts on fungal root endophytes. Fungal taxa that were common at high elevations declined most under climate warming, whereas low elevation dominants responded neutrally or increased with experimental warming. Altitudinal gradients in fungal communities were strongly specific to the plant host species. Specifically, Poa species had 25–60% greater fungal isolate abundance and 25–38% greater fungal diversity at high elevations than at low elevation sites. In contrast, Festuca thurberi had 64% lower fungal diversity on roots at high elevation than at low elevation. Our results help to improve understanding of the potential for climate change to alter plant-fungal interactions in mountain ecosystems.